Weak environmental integration in Peru - Alcalde, Gonzalo (2025)
In 21st-century Peru, decisions about development —even at high levels of government— still do not fully consider the environmental dimension. This occurs despite progress in environmental institutions since the 1990s, and despite official discourses and instruments that are ostensibly aligned with sustainable development. This omission has been especially evident at critical moments in the last decade, when existing environmental regulation has been weakened. This essay proposes that the policy coherence framework for sustainable development (PCSD) —still rarely used domestically— makes it possible to identify different points where the integration of environmental issues into development decisions needs to be strengthened. In this sense, it is argued that the most urgent pending agenda refers not only to the environmental policy space, but also to points in the policy process where coherence between the major policy spaces (economic, social, environmental) and coherence between national decisions and the country’s international commitments can be ensured.